Estimating the age of Heliconius butterflies from calibrated photographs - Denise Dalbosco Dell’Aglio; Derya Akkaynak; W. Owen McMillan; Chris D. Jiggins (PeerJ, 2017)
Mating behaviour and predation avoidance in Heliconius involve visual colour signals; however, there is considerable inter-individual phenotypic variation in the appearance of colours. In particular, the red pigment varies from bright crimson to faded red. It has been thought that this variation is primarily due to pigment fading with age, although this has not been explicitly tested. Previous studies have shown the importance of red patterns in mate choice and that birds and butterflies might perceive these small colour differences. Using digital photography and calibrated colour images, we investigated whether the hue variation in the forewing dorsal red band of Heliconius melpomene rosina corresponds with age. We found that the red hue and age were highly associated, suggesting that red colour can indeed be used as a proxy for age in the study of wild-caught butterflies.